Polycyclic aromatic hydrocarbons in PM2.5 and PM10 atmospheric particles in the Metropolitan Area of Costa Rica: Sources, temporal and spatial variations - Solórzano Arias, David (2017)
Polycyclic aromatic hydrocarbons (PAHs) concentrations in PM10 and PM2.5 particles were measured at 14 monitoring sites (12 for PM10 and 2 for PM2.5), located in the Metropolitan Area of Costa Rica, from January to November 2013. High-volume air samplers with pretreated quartz filters were used to collect the particles. The analytical determination was carried out using high-performance liquid chromatography (HPLC). The most abundant PAHs were benzo[a]anthracene, indeno(1,2,3-cd)pyrene, dibenz[a,h]anthracene and acenaphthylene. Ratios obtained by correlating the concentration of some PAHs, both PM10 and PM2.5, suggest that gasoline and diesel vehicles are the main sources in the area being studied. This is consistent with the results obtained when applying the positive matrix factorization (PMF) analysis, since vehicles accounted for 62–74% of total emissions in the area; burning wood fuel was the second source of emissions, contributing between 7 and 15%; and road dust was third, with almost 8%.